If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -1(2n + -9) = 3 + -3n Reorder the terms: 10 + -1(-9 + 2n) = 3 + -3n 10 + (-9 * -1 + 2n * -1) = 3 + -3n 10 + (9 + -2n) = 3 + -3n Combine like terms: 10 + 9 = 19 19 + -2n = 3 + -3n Solving 19 + -2n = 3 + -3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '3n' to each side of the equation. 19 + -2n + 3n = 3 + -3n + 3n Combine like terms: -2n + 3n = 1n 19 + 1n = 3 + -3n + 3n Combine like terms: -3n + 3n = 0 19 + 1n = 3 + 0 19 + 1n = 3 Add '-19' to each side of the equation. 19 + -19 + 1n = 3 + -19 Combine like terms: 19 + -19 = 0 0 + 1n = 3 + -19 1n = 3 + -19 Combine like terms: 3 + -19 = -16 1n = -16 Divide each side by '1'. n = -16 Simplifying n = -16
| -4(z-9)-(8-3z)=-2z | | x^2-6x+5=1 | | 13+27=-5(5x-8) | | 6=1.12 | | 54+x=33.7 | | 6ln(6x)=24 | | 0.002+0.03=0.92 | | 85+5n=20 | | 0.4+1.3=15 | | 9x+18=9(x+2) | | y=7x-28+x | | 100000=20x+20000 | | 36-11x=-8x-39 | | -(x+3)+.75x+5=0 | | 6-(x+6)=6-3(x+4) | | 9-x=-3x+-3 | | -12+2=11 | | 4x^2=8x+16 | | 7-(8x-3)=-6x | | 0=-9x^2+6x+3 | | 8+3(x+2)=8(5+2x) | | 4x-136=3x+30 | | 24=9x+x^2 | | 5(x+2)=-3(x+2) | | w^2-4w+5=0 | | 7+3(18-13)= | | (3x-2)(x+10)=0 | | 7(x-9)=-8(x+1)+5 | | 60000=150x+5000 | | 94-6x=-80-12x | | 10000=150x+5000 | | 29+72+x=180 |